2018
DOI: 10.1111/nph.15098
|View full text |Cite
|
Sign up to set email alerts
|

Amplification and adaptation of centromeric repeats in polyploid switchgrass species

Abstract: Centromeres in most higher eukaryotes are composed of long arrays of satellite repeats from a single satellite repeat family. Why centromeres are dominated by a single satellite repeat and how the satellite repeats originate and evolve are among the most intriguing and long-standing questions in centromere biology. We identified eight satellite repeats in the centromeres of tetraploid switchgrass (Panicum virgatum). Seven repeats showed characteristics associated with classical centromeric repeats with monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 60 publications
4
30
1
Order By: Relevance
“…2014 ). Based on these findings, along with the presence of partially homogenized centromeric satellites in switchgrass species ( Yang et al. 2018 ), it was hypothesized that evolutionarily young centromeres may be repeat-free and only later accumulate random satellites that are subsequently homogenized across different chromosomes, resulting in the selection of a single, structurally favorable repeat to dominate all centromeres ( Gong et al.…”
Section: Discussionmentioning
confidence: 99%
“…2014 ). Based on these findings, along with the presence of partially homogenized centromeric satellites in switchgrass species ( Yang et al. 2018 ), it was hypothesized that evolutionarily young centromeres may be repeat-free and only later accumulate random satellites that are subsequently homogenized across different chromosomes, resulting in the selection of a single, structurally favorable repeat to dominate all centromeres ( Gong et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Robicheau et al [ 61 ] report rDNA sequences appearing at multiple sites on chromosomes without forming rDNA arrays, presence of centromere-associated rDNA hits, and divergence of these sequences to pseudogenes. Yang et al [ 62 ] even demonstrated that a 5S ribosomal RNA gene array was recruited to be the functional centromere for one of the switchgrass chromosomes, making Pv156 repeat the most enriched centromeric repeat. Thereafter, association of rDNA sequences with the centromeric region of C. gigas ( Table S2 ) is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…rDNA tracts can serve as an origin of satellite repeats [ 50 , 51 ], and centromerically located satellite DNA partially derived from 5S rDNA was described, for instance, in the frog Physalaemus cuvieri [ 52 ]. Remarkably, in the switchgrass Panicum virgatum it was recently shown that one of its centromeres propagated the exact 5S rDNA unit with its completely conserved 5S rRNA gene sequence and NTS region into functional centromeric DNA, without obstructing the fundamental function of the 5S rRNA genes [ 53 ]. We believe a similar scenario could be assumed in T .…”
Section: Discussionmentioning
confidence: 99%